2001
DOI: 10.1143/jjap.40.5722
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Electrical Properties of Lead-Free Piezoelectric Material (Na1/2Bi1/2)TiO3–BaTiO3

Abstract: Single crystals of lead-free piezoelectric material x(Na1/2Bi1/2)TiO3–yBaTiO3 (NBBT 100x/100y) have been successfully grown by the flux method and the Bridgman method. Using the flux method, crystals having an edge length of 2–8 mm were obtained using Bi2O3 flux with cooling from 1350°C to 800°C at a rate of 3.5°C/h. Using the Bridgman method, comparatively good crystal of 15 mm diameter and 50 mm length was obtained using Bi2O3 flux with the Pt crucible driven down through the heat zone at a speed of 1.0 mm/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(84 citation statements)
references
References 7 publications
1
83
0
Order By: Relevance
“…Extensive studies of (Na 1/2 Bi 1/2 ) 1 À x Ba x TiO 3 (NBT-BT) piezoelectrics have demonstrated their potential as substitute for lead zirconate titanate materials [1][2][3][4] and clarified many uncertain points in their phase diagram. 1,[5][6][7][8][9][10][11] Detailed structural investigations by neutron diffraction 12 evidenced the polymorphic structure of (Na 1/2 Bi 1/2 )TiO 3 (NBT) that, above 810 K, belongs to the cubic symmetry (space group Pm 3m), while below 810 K and down to about 600 K, a tetragonal P4bm phase is established and further transforms into the rhombohedral R3c ground state; the boundaries between these states are not sharp, and broad regions of phase coexistence have been found.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies of (Na 1/2 Bi 1/2 ) 1 À x Ba x TiO 3 (NBT-BT) piezoelectrics have demonstrated their potential as substitute for lead zirconate titanate materials [1][2][3][4] and clarified many uncertain points in their phase diagram. 1,[5][6][7][8][9][10][11] Detailed structural investigations by neutron diffraction 12 evidenced the polymorphic structure of (Na 1/2 Bi 1/2 )TiO 3 (NBT) that, above 810 K, belongs to the cubic symmetry (space group Pm 3m), while below 810 K and down to about 600 K, a tetragonal P4bm phase is established and further transforms into the rhombohedral R3c ground state; the boundaries between these states are not sharp, and broad regions of phase coexistence have been found.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the most studies has been focused on improving its piezoelectric proprieties by fabricating NBT-based solid solutions, such as ͑1−x͒͑Na 0.5 Bi 0.5 ͒TiO 3 − xBaTiO 3 , 6,7 and NBT single crystal. 8,9 Compared with NBT ceramic, NBT single crystal presents good piezoelectric properties and rich optical properties. 5,[8][9][10][11] Ge et al, 10 reported an optical property of a large-size NBT single crystal fabricated by using top-seededsolution growth method.…”
Section: Introductionmentioning
confidence: 99%
“…5,[8][9][10][11] Ge et al, 10 reported an optical property of a large-size NBT single crystal fabricated by using top-seededsolution growth method. Although a NBT single crystal has been fabricated by using different growth methods, 5,[8][9][10][11] the theoretical study on its electronic structure is seriously limited. There is also disparity between different theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric broadening of the peak suggests spreading of relaxation with temperature. This indicates that relaxation in the material is temperature dependent [29]. The value of Z max decreases with increasing temperature, indicating a decrease in the bulk resistance.…”
Section: Complex Impedance Analysismentioning
confidence: 92%